Graft kidney hydronephrosis caused by transplant ureter inguinal hernia: A case report. Issue 21 (28th May 2021) - Chang, Tian-You; Chang, Chao-Hsiang; Lai, Ping-Chin; Lin, Wei-Ching
Abstract: Rationale: Ureteral obstruction of the graft kidney is a common complication of kidney transplantation. However, ureteral obstruction caused by inguinal hernia has rarely been reported. We present a rare case of ureteral obstruction with allograft dysfunction caused by an inguinal hernia. Patient concerns: A 76-year-old man, who was a renal transplant recipient, presented with bilateral pitting oedema, reduced urine output, and right inguinal hernia. Diagnoses: Abdominal computed tomography revealed severe hydroureteronephrosis of the kidney allograft. A right inguinal hernia with ureteral incarceration was observed. Interventions: The patient underwent graft percutaneous nephrostomy, followed by antegrade insertion of a double-J tube (DJ). Gradual improvement was observed in his renal function. Right inguinal herniorrhaphy was performed 5 days later. Outcomes: The renal function returned to normal after percutaneous nephrostomy and insertion of the DJ. A right inguinal direct-type hernia with ureter adhesion to the hernial sac was observed during the surgery. The posterior wall defect was repaired by the McVay technique. The DJ was removed after 1 month. The patient's renal function remained stable at 6-month follow-up. Lessons: The orientation of the graft kidney has a significant influence on the location of the ureter. Upward orientation of the hilum will result in superficial location of the ureter, rendering it close to the hernial sac and susceptible to incarceration. The transplant surgeon should be aware of such a presentation of graft dysfunction with inguinal hernia to prevent a delay in the diagnosis and graft loss.